Effects of Provider Support and Psychosocial Stressors on Maternal Health-promoting Behaviors - (:unkn) unknown (My University, 2021)
ABSTRACTEFFECTS OF PROVIDER SUPPORT AND PSYCHOSOCIAL STRESSORS ON MATERNAL HEALTH-PROMOTING BEHAVIORS Despite technological and structural advances in the organization and delivery of health care services to pregnant women and infants, the U.S. ranks low on perinatal outcomes with profound disparities. Engagement in health-promoting behaviors during pregnancy is critical in improving birth outcomes. Women, particularly women of color, continue to experience unmet needs for emotional support with providers. Women of color experience being treated differently based on their race. The purpose of this study was to 1) examine the relationships between stress, provider support, and specific maternal health promoting behaviors (MHPB) in pregnancy and, 2) explore the potential mediating/moderating influence of perceived racial discrimination (PRD) on the relationship of stress and specific MHPBs. Methods: Retrospective analysis of pooled (2004-2015) Pregnancy Risk Assessment Monitoring Survey (PRAMS) national data. Main outcomes included health behaviors of smoking, alcohol use, breastfeeding, family planning and a composite index of MHPB. Analysis employed Stata® 15 survey procedures and included bivariate and multiple logistic regression. Generalized structural equation models (GSEM) were used to explore possible mediating/moderating effects of PRD. Results: The overall sample of 88,935 consisted of 68% Non-Hispanic (NH) White, 13% NH-Black, 13% Hispanic, and 7% NH-other with most respondents (56%) between 25-34 years of age. Perceived high stress was associated with significantly greater adjusted odds of smoking (Odds Ratio [OR]: 8.0, 95% Confidence Interval [CI]:6.04-10.78), and lower odds of family planning use (OR: 0.78, CI: 0.69-0.88), and overall lower odds of scoring high on MHPB (OR: 0.33, CI: 0.29-0.38). Provider support was associated with decreased adjusted odds of smoking and about 15% increased odds of scoring higher on MHPB (OR: 1.15, CI: 1.07-1.25). PRD, analyzed on a separate sample in the data, did not moderate the relationship between stress and health promoting behaviors outcomes. Mediation results showed a significant indirect effect of PRD with breastfeeding and family planning. Conclusion: This study demonstrates that provider support during pregnancy might promote engagement in health-enhancing behaviors and that PRD could have unique effects on stress and health behaviors in pregnancy. Further examination of these relationships could increase understanding and lead to the adoption of enhanced models of care.
Keywords: Health Behaviors; Healthcare Providers; Perceived Racial Discrimination; Pregnancy; Stress